Weighted kernel regression in solving small sample problems for regression framework and its variants - Mohd. Ibrahim Shapiai @ Abd. Razak, 1983-; Rubiyah Yusof; Zuwairie Ibrahim, supervisor; Fakulti Kejuruteraan Elektrik (2014)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2014